2018
DOI: 10.1111/jace.15753
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion luminescence enhancement of NaYF4:Yb3+,Er3+ nanocrystals induced by the surface plasmon resonance of nonstoichiometric WO2.72 semiconductor

Abstract: Upconversion luminescence of rare‐earth ions doped nanoparticles can be enhanced by the localized surface plasmon resonance (LSPR) of noble metals nanoparticles, which was extensively investigated. The semiconductor nanomaterials such as the WO2.72 exhibited the tunable LSPR, which provide the possibility for the luminescence enhancement of upconversion nanoparticles. In this work, the urchin‐like WO2.72 was successfully prepared by solvothermal method, exhibiting the LSPR in the near infrared region. The infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…(10, 8, and 12 times) in the luminescence of UCNPs at 525, 542, and 660 nm, respectively. [36] This may be attributed to the strong LSPR effect that originated from WO 2.72 . Li's group developed the UCNPs/WO 3−x hybrid, which has a stronger upconversion emission.…”
Section: Photoluminescence Modulationmentioning
confidence: 99%
“…(10, 8, and 12 times) in the luminescence of UCNPs at 525, 542, and 660 nm, respectively. [36] This may be attributed to the strong LSPR effect that originated from WO 2.72 . Li's group developed the UCNPs/WO 3−x hybrid, which has a stronger upconversion emission.…”
Section: Photoluminescence Modulationmentioning
confidence: 99%
“…44 When NaYF 4 :Yb 3+ ,Er 3+ was coupled with urchinlike WO 2.72 , the UCL was enhanced by 10, 8, and 12 times at 525, 542, and 660 nm, respectively. 48 Sandwichtype layered film composed of Cs x WO 3 , NaYF 4 , and NaYF 4 :Yb 3+ ,Er 3+ showed that the UCL enhancement depends on the thickness of the UCNPs and Cs x WO 3 layers, and the optimal enhancement of UCL reached 144 times. 45 The LSPR resonance absorption of MWO 3 is affected by the type, morphology, and size of MWO 3 , and the different MWO 3 / UCNP systems have different enhancement effects and different enhancement mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…Enhanced UCL was realized by building layered structures W 18 O 49 /NaYF 4 :Yb 3+ ,Er 3+ and applying them to improve photocatalysis . When NaYF 4 :Yb 3+ ,Er 3+ was coupled with urchinlike WO 2.72 , the UCL was enhanced by 10, 8, and 12 times at 525, 542, and 660 nm, respectively . Sandwich-type layered film composed of Cs x WO 3 , NaYF 4 , and NaYF 4 :Yb 3+ ,Er 3+ showed that the UCL enhancement depends on the thickness of the UCNPs and Cs x WO 3 layers, and the optimal enhancement of UCL reached 144 times .…”
Section: Introductionmentioning
confidence: 99%
“…Their results provide a new strategy for improving luminescent materials and highlight the novel application in photonics. Yang and his co-workers prepared the urchin-like WO 2.72 which showed the LSPR in the near-infrared region and realized the increase of the UC luminescence due to the WO 2.72 film-enhanced excitation field [ 165 ]. Gao and his co-workers prepared core-shell hybrid structure Cu 1.8 S@NaYF 4 : X%Yb 3+ @NaYF 4 : Yb 3+ , Er 3+ , and they further enhanced the LSPR-coupled UC luminescence by adjusting the intermediate spacer NaYF 4 : X%Yb 3+ and Yb 3+ concentration.…”
Section: New Strategiesmentioning
confidence: 99%